1994
DOI: 10.1159/000227374
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Piroxicam and Esculetin on Incidence, Proliferation, and Cell Kinetics of Mammary Carcinomas Induced by 7,12-Dimethylbenz[a]anthracene in Rats on High- and Low-Fat Diets

Abstract: We investigated the effects of piroxicam, a cyclooxygenase inhibitor, and esculetin, a lipoxygenase inhibitor, on 7,12-dimethylbenz[a]anthracene (DMBA)-induced mammary carcinogenesis in female rats. Seven days after receiving a 5-mg dose of DMBA, rats were fed either a high-fat (20% soybean oil) or low-fat (0.5% soybean oil) diet. One third of the rats received diets containing 0.01% piroxicam and one third received diets containing 0.03% esculetin. Esculetin significantly inhibited mammary tumorigenesis and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…However, Kitagawa and Noguchi found that piroxicam, one of the NSAIDs, had no inhibitory effect on DMBA-induced mammary carcinogenesis. 24) Usual NSAIDs inhibit both COX-1 and -2, and induce stomach ulcers and renal dysfunction as side effects. Recently, selective COX-2 inhibitors, which have few side effects, have attracted the attention of many researchers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Kitagawa and Noguchi found that piroxicam, one of the NSAIDs, had no inhibitory effect on DMBA-induced mammary carcinogenesis. 24) Usual NSAIDs inhibit both COX-1 and -2, and induce stomach ulcers and renal dysfunction as side effects. Recently, selective COX-2 inhibitors, which have few side effects, have attracted the attention of many researchers.…”
Section: Discussionmentioning
confidence: 99%
“…24) We decided to compare the effects of nabumetone, a cyclooxygenase inhibitor, and esculetin, a lipoxygenase inhibitor. Though the carcinogen which we used, MNU, was different from the one they used, the results in this study were similar to theirs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21) Furthermore, it has been reported that esculetin inhibits mammary carcinogenesis. 22,23) 1,2-Dimethylhydrazine (DMH) is an alkylating carcinogen that causes neoplastic changes in colonic mucosa at a level proportional to the quantity of methylated DNA adducts induced in colonic crypt cells.24) DMH-induced colon tumors are currently the most popular models in which to study the morphology, pathogenesis, prevention, and treatment of colorectal cancer.25) Aberrant crypt foci (ACF), first observed in the colonic mucosa of carcinogen-treated rodents, 26) are considered to be preneoplastic lesions, 27) since they are observed at high frequency in the colonic mucosa of patients with colon cancer 28) and rodents treated with colon carcinogens. …”
mentioning
confidence: 99%
“…27,28 Another study showed that esculetin and esculin can protect biomolecules from oxidative damage generated in the initial process of carcinogenesis. 29,30 Thus, the mass fraction of seeds of D. odorata is a rich source of coumarin and esculin, showing high levels of concentration of these compounds. These compounds are consumed in the preparations of D. odorata, and although there is evidence of beneficial effects against cancer, they remain a potential source of harmful xenobiotics to humans.…”
Section: Derivatization With Silylationmentioning
confidence: 99%